Identification and management of “delirious mania:” A rare clinical entity - Nishtha Chawla (Industrial Psychiatry Journal, 2018)
Little is known about the entity of delirious mania, apart from a few reports. Delirious mania, though a potentially lethal condition, has not found a place in the current classification system. We discuss the approach to the identification and management of delirious mania in a female patient presenting with catatonic and delirious features, with a past history of recurrent mood episodes. However, it must be emphasized that it is likely to be a rare clinical presentation of bipolar disorder and should not be the first diagnostic consideration. As a rule, any patient presenting with delirium or clouded consciousness first warrants a thorough medical workup and other specialty referrals.